Validitas dan Reliabilitas Ujian SOCA (Students Oral Case Analysis): Studi di Salah Satu Fakultas Kedokteran di Indonesia - Rizka Aries Putranti; Ova Emilia; Efrayim Suryadi (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2016)
Background: Medical faculty has to make sure that the students meet the minimal competence needed using apropriate exam. While the exam itself should facilitate students to learn. Oral examination has known for its ability to facilitate students learn but low in validity and reliability. Medical faculty of Lampung University (FK Unila) apply the student oral case analysis (SOCA) exam as one of block assessment component, as with MCQ, tutorial, and laboratory exam. This study aimed to evaluate validity and reliability of SOCA examination at FK UnilaMethod: Video of 65 students doing SOCA examination and 28 question rubrics had taken when odd semester exam year 2014-2015 has been carying out at FK Unila. Video and question rubrics were assessed by 5 panelis and analysed using Lawshe's content validity ratio (CVR) to determinate its content validity. Students performance on the video were re-assessed by another assessor to see inter-rater reliability, than analysed using kappa Cohen. Two expert in medical education assessed the cognitive comlpexity of the question rubrics. Data of SOCA's student's mark from year II, III, and IV were analysed for construct valdity and internal consistency.Results: 93,7% of the overall question in 65 video were valid (CVR>99%) and 71,8% question number in 28 question rubrics also valid according to 5 panelis. SOCA cognitive complexity were at level of analyse, know how and 4a. Inter-rater reliability analysis showed 0,549 (moderate agreement) kappa value. Mann Whitney analysis for construct validity showed no significant difference of all year. Cronbach alpha analysis showed internal consistency at the point 0,575.Conclusion: FK Unila's SOCA of odd semester examination year 2014-2015 has sufficient content validity, sufficient cognitive complexity and sufficent inter-rater reliability but lack in construct validity and internal consistency. Keywords: SOCA, validity, reliability